Innovation Barriers and Proactive Work Behaviour: Lessons from Selected Hotels in Nairobi City, Kenya - Shirandula, Duncan (Utafiti Foundation, 2017)
Proactive work behaviour and innovation in hotels may bring about positive changes in work environment that may include improved quality products, increased efficiency, a cut on costs and a greater market share. Despite these benefits, hotels struggle to be proactive and innovative; but fail because of challenges brought about in particular by innovation barriers for instance governmental constraints, lack of competences, time and risks of failure. These innovation barriers may lessen employees’ personal initiative, ability to take charge, sell their issues and voice their views in the organization. Thus, this book presents the findings of a study that was guided by the objective: to determine the relationship between innovation barriers and proactive work behaviour in selected hotels located in Nairobi city. The study examined endogenous and exogenous innovation barriers in relation to proactive work behaviour in the hospitality industry. The study also tested the difference in proactive work behaviour between the male and female employees. The study employed a co-relational research design and was conducted in Nairobi city. The findings of the study indicated a relationship between endogenous innovation barriers and proactive work behaviour (t=-5.036, p<.000). It was established that there was a relationship between exogenous innovation barriers and proactive work behaviour (t=3.503, p<.0.01). There is no difference in proactive work behaviour between male employees and female employees (F 1.312; p. = 0.269). The study concluded that both endogenous and exogenous innovation barriers may affect proactive behaviour at work place. It recommended that hotels should focus on creating an enabling work environment that promotes proactive work behaviour through provision of adequate job resources. Besides, organisations should embrace gender diversity at workplace to create broader search base for proactive work behaviour. xi Innovation Barriers & Proactive Work Behaviour This book targets the stakeholders in the hospitality industry in Kenya, Africa and globally. The general readers are also important audience of the book. The results presented here could give a baseline on which any corrective action could be taken in the industry. On the organisation of the book, it begins by giving an overview on the proactive work behaviour, innovation and endogenous and exogenous barriers to innovation in general terms. An in-depth discussion on the concept of innovation is given in chapter two of the book, after which the proactive work behaviour is discussed with intensive review of existing literature. Chapter four discusses proactive work behaviour and gender differences. A study of the selected hospitality establishments (Hilton, Safari Park and Intercontinental hotels) follows in chapter five and the discussion of the findings is given in chapters six and seven. Lastly, conclusion drawn and recommended ways through which innovation can be enhanced with combating the endogenous and exogenous barriers in relation to proactive work behaviour follows in chapter seven.
Keywords: Work behaviour; Innovation